Pembuatan Dan Analisis Motion Graphic Teknik Kinetic Typography Sebagai Media Edukasi Protokol Pencegahan Covid-19 Di Pt. Uni Metaltech Industry - Annisa S (Politeknik Negeri Batam, 2021)
One way to maintain the economic aspect of the Batam industry in the midst of the Covid-19 pandemic is to keep employees working in one way, namely WFH (Work From Home). However, this cannot be done immediately because it will have an effect on companies that cannot carry out the protocol. So in order to run the company to help the economic crisis that occurred, PT. The Metaltech Industry Union still has to stay operational. This of course can create new problems, if employees are free to act as usual without any precautionary protocols. Therefore, it is necessary to implement a good and effective prevention protocol.Based on these problems, a study was conducted in the form of a motion graphic product as an educational media for the protocol for making COVID-19 prevention at PT. Metaltech Industry Union and analysis was carried out afterwards. The research method used is the quantitative method with the Villamil-Molina settlement method (Development, Preproduction, Production, Post Production, Delivery). The results of product testing that have been made to experts get a Likert scale score of 3.76